2006
DOI: 10.1051/0004-6361:20065438
|View full text |Cite
|
Sign up to set email alerts
|

Catalogue of far-infrared loops in the Galaxy

Abstract: Aims. An all-sky survey of loop-and arc-like intensity enhancements has been performed to investigate the large-scale structure of the diffuse far-infrared emission. Methods. We used maps made of 60 and 100 µm processed IRAS data (Sky Survey Atlas and dust infrared emission maps) to identify large-scale structures: loops, arcs, or cavities, in the far-infrared emission in the Galaxy. Distances were attributed to a subsample of loops using associated objects. Results. We identified 462 far-infrared loops, analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 48 publications
0
47
0
1
Order By: Relevance
“…About 50 percent of the clumps are located on FIR loops (Könyves et al 2007) that are boundary regions (shells) around the voids in the galactic ISM. A preliminary analysis of a sample of sources and their AKARI FIR photometry showed that the clumps located on the shells have ∼20% higher probability of being associated with YSO candidates (Marton 2012).…”
Section: Connection With Star Formationmentioning
confidence: 99%
“…About 50 percent of the clumps are located on FIR loops (Könyves et al 2007) that are boundary regions (shells) around the voids in the galactic ISM. A preliminary analysis of a sample of sources and their AKARI FIR photometry showed that the clumps located on the shells have ∼20% higher probability of being associated with YSO candidates (Marton 2012).…”
Section: Connection With Star Formationmentioning
confidence: 99%
“…IRAS loops were identified by Könyves et al (2006) in the framework of an investigation of the large-scale structure of the diffuse ISM, started by Kiss et al (2004) using the 60 and 100 μm ISSA data (IRAS Sky Survey Atlas, Wheelock et al 1994). Galactic infrared loops (GIRLs, Könyves et al 2006) by definition must show an excess far-IR intensity confined to an arc-like feature extending to at least 60% of a complete ellipseshaped ring.…”
Section: Iras Loopsmentioning
confidence: 99%
“…Galactic infrared loops (GIRLs, Könyves et al 2006) by definition must show an excess far-IR intensity confined to an arc-like feature extending to at least 60% of a complete ellipseshaped ring. The thicknesses of the rings are given in the catalogue for all GIRLs.…”
Section: Iras Loopsmentioning
confidence: 99%
“…The evolution of bubbles and super bubbles produced by supernovae explosions and stellar winds of association are the primary processes that determine the structure and energetic of all components of the diffused interstellar medium. [4,5] identified 462 Far infrared loops using 100 and 60 µm IRAS maps. They studied their size, luminosity, distributions and concluded that these structures are formed and governed by supernovae and stellar winds at the low galactic latitude.…”
Section: Introductionmentioning
confidence: 99%